Genetic diversity of the orange-spotted grouper (Epinephelus coioides) in Terengganu Malaysia based on mitochondrial cytochrome b sequence data - Shaidatul Nadia Waludin,; Ahmad Azfar Mohamed,; Ing, Chia Phang; Yukinori Mukai, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Orange-spotted groupers (Epinephelus coioides) are marine fish which can be found in the state of Terengganu (in Malaysia) and are economically important. Overfishing and fish farmers’ dependency on wild orange-spotted grouper seed fish have caused a decline in their numbers. Hence, the aim of this study was to investigate the genetic diversity of wild orange-spotted grouper populations in Terengganu via partial cytochrome b (cyt-b) gene analysis. A total of 60 fish, which were reared from wild seed fish, were collected from farms in Besut and Setiu, Terengganu. Their DNA was extracted using the Qiagen Blood and Tissue kit. PCR amplification was conducted using cyt-b primers, and a sequence of 460 bp in length was obtained for each sample. Next, phylogenetic analysis was performed to study the relationships among the individuals. The haplotype and nucleotide diversities of the populations were investigated to measure genetic diversity. The haplotype diversity (Hd) of E. coioides was relatively low for both Besut (Hd = 0.4161) and Setiu (Hd = 0.8782) populations. The nucleotide diversity (π) for both Besut and Setiu populations was also low. Moreover, 15 haplotypes were identified among the 60 individuals, with 33 individuals sharing a single haplotype (Hap01). These findings similar with a previous study that reported that seed fish dependent can led to a decline in grouper numbers and in turn cause genetic deprivation in the population.